Longitudinal cohort study of depression, post-traumatic stress, and alcohol use in South African women who attend alcohol serving venues. - Abler, Laurie A; Sikkema, Kathleen J; Watt, Melissa H; Eaton, Lisa A; Choi, Karmel W; Kalichman, Seth C; Skinner, Donald; Pieterse, Desiree (BMC psychiatry, 2014)
BackgroundIn South Africa, alcohol use poses a public health burden. Hazardous alcohol use often co-occurs with psychological distress (e.g., depression and post-traumatic stress). However, the majority of the research establishing the relationship between alcohol use and psychological distress has been cross-sectional, so the nature of co-occurring changes in psychological distress and alcohol use over time is not well characterized. The objective of this study is to examine the longitudinal relationship between psychological distress and alcohol use among South African women who attend alcohol serving venues.MethodsFour waves of data were collected over the course of a year from 560 women in a Cape Town township who attended drinking venues. At each assessment wave, participants reported depressive symptoms, post-traumatic stress symptoms, and alcohol use. Multilevel growth models were used to: 1) assess the patterns of alcohol use; 2) examine how depressive symptoms uniquely, post-traumatic stress symptoms uniquely, and depressive and post-traumatic stress symptoms together were associated with alcohol use; and 3) characterize the within person and between person associations of depressive symptoms and post-traumatic stress symptoms with alcohol use.ResultsWomen reported high levels of alcohol use throughout the study period, which declined slightly over time. Post-traumatic stress symptoms were highly correlated with depressive symptoms. Modeled separately, both within person and between person depressive and post-traumatic stress symptoms were uniquely associated with alcohol use. When modeled together, significant between person effects indicated that women who typically have more post-traumatic stress symptoms, when controlling for depressive symptoms, are at risk for increased alcohol use; however, women with more depressive symptoms, controlling for post-traumatic stress symptoms, do not have differential risk for alcohol use. Significant within person effects indicated an interaction between depressive and post-traumatic stress symptoms; women reported more alcohol use than usual at times when they had higher post-traumatic stress symptoms, and this increase in alcohol use was further exacerbated for women who also had higher depressive symptoms than usual.ConclusionsThese findings suggest that interventions targeting post-traumatic stress, especially when post-traumatic stress is comorbid with depression, may reduce alcohol use among South African women who drink.